Implementation of api chat messenger in the integrated presence system at Nur Azizi Tanjung Morawa private high school - Hutagalung, Gabriel Ardi; Sembiring, Zakaria; Safitri, Habibi Ramdani; Aswani, Aprilza; Khairani, Ade Irma (Jurnal Mandiri IT, 2025)
Development of an Integrated Attendance System at the Private Senior High School (SMA) Nur Azizi Tanjung Morawa: Messenger API Integration to Improve Parent-Guardian Communication and Monitor Student Attendance in Real-Time. Advances in information and communication technology have influenced various aspects of life, including education. One technology implementation that is increasingly common is a Radio Frequency Identification (RFID) based attendance system. However, although this system provides the advantage of automatically recording student attendance, delays in providing information to parents regarding student attendance is a major obstacle. To overcome this problem, this research aims to develop and implement a messenger API in the attendance system at Nur Azizi Tanjung Morawa Private High School. This integration is expected to strengthen communication between schools and parents and monitor student attendance in real-time.